Factors That Determine the Nature of Relationship between Mothers and Their Daughters In-Law: A Content Analysis of the ‘Mother In-Law’ Tv Drama Series - Orawo , Doreen Akech; Kutotto , Patrick Lumumba; Kafu , Joyce (African Journal of Education,Science and Technology (AJEST), 2017)
The relationship between mothers and their daughters-in-law remains of a strained nature despite the negative impacts it has on communication routines of families. While existing studies focus more on the dyadic relationships, there is a need to determine why this relationship has to be strained. This study therefore examined factors that determine the nature of the relationship between a mother and her daughter’s in-law as portrayed in family drama. Critical content analysis was used to analyze eight episodes of the ‘Mother-in-Law’ TV drama series aired on citizen TV. The episodes were sampled purposively basing on their composition of mother and daughter in-law scenes. Two coders conducted partial transcription of the episodes by playing back, recording and writing the content of the episodes. The summarized transcripts were then analyzed for content. Scott’s pi inter coder reliability value of 0.82 revealed that there was high agreement among the two coders on transcription. Content analysis revealed that independence, family identity, supportive communication, sense of belonging, accommodation, and cultural orientation are critical factors in the relationship between a mother and her daughters-in-law. Provision of an environment that can support these factors could therefore go a long way to improving the strained relations and hence communication routines of families.